Exploring genetic alterations and protein marker expression in cancer: investigating ARID1A and SMARCA4 knock-outs in colorectal cancer and evaluating histological markers for targeted therapy in ovarian cancer - Jin, Xiaoxi; Jin, Cici (The University of Edinburgh, 2025)
This dissertation presents two distinct yet connected research projects focused on the alteration and evaluation of DNA and protein expression in common cancers, both of which are subjects of ongoing research into their mechanisms and potential therapeutic advancements. Colorectal cancer, one of the most prevalent and deadly cancers globally involves metastasis and therapy resistance driven largely by tumour plasticity, which is affected by changes in the expression of epigenetic modifying proteins. Ovarian cancer, on the other hand, is common among women and exhibits various histotypes that differ in their origin, tumour microenvironment, and genetic and epigenetic expressions. Both cancers stand to benefit from further study to facilitate the development of new treatments. The first project focuses on producing SWI/SNF CRISPR/Cas9 knockouts in a mouse colon organoid line (Apcfl/fl;KrasLSL-G12D/+;Trp53fl/fl). Knockouts were validated using qPCR and Western blot analysis. Incomplete knockouts were produced, indicating the need for further evaluation using DNA sequencing. Additional knockout experiments are recommended, utilising the existing protocol with different clones picked from the lentiviral transduction pool. The second project involved the use of TMAs (tumour microarrays) taken from patients with different ovarian cancer histotypes. These TMAs were sectioned and stained for membrane proteins that are potential targets for antibody-drug conjugate (ADC) therapy. The TMAs were then scored by two independent assessors for the expression of these targets, providing a foundation for future studies exploring the suitability of ADC treatments in different patient demographics and ovarian cancer histotypes, as well as the role of target expression levels. Though these two projects investigate different types of cancer, together they provide a broad foundation in research methods and the diverse skills required for cancer research. Both projects contribute valuable groundwork for future studies on the mechanisms and treatment of colorectal and ovarian cancers.
Keywords: Colorectal cancer; Ovarian cancer; CRISPR/Cas9; Tumour microarrays (TMAs); Antibody-drug conjugate (ADC) therapy